Puya cahuachensis (Bromeliaceae, Puyopsis), a new species from Southern Peru - Galán De Mera, Antonio; Montoya, Juan; Orellana, José A. Vicente; Perea, Eliana Linares (Phytotaxa, 2016)
A new species, Puya cahuachensis, is described and illustrated. It can be distinguished from its closely related species P. weberbaueri by the longer leaves with retrorse brown spines, erect peduncles, a lax inflorescence with long subcylindrical spirally arranged branches exceeding primary bracts, an inflorescence with a soft white woolly pubescence that does not fully mask the greyish colour of the rachis, and greenish bracts and sepals at anthesis.